ANALISIS MANAJEMEN K3 UNTUK MENGIDENTIFIKASI BAHAYA KERJA MENGGUNAKAN HIRARC (Hazard Identification, Risk Assessment, and Risk Control) PADA PT PAGILARAN : ANALISIS MANAJEMEN K3 UNTUK MENGIDENTIFIKASI BAHAYA KERJA MENGGUNAKAN HIRARC (Hazard Identification, Risk Assessment, and Risk Control) PADA PT PAGILARAN - Prayitno, Teguh; Utami, Indah Wahyu; Diansari, Brillian Nur (Journal Science Innovation and Technology (SINTECH), 2025)
In every industrial sector, especially in manufacturing, where there is always a risk of accidents and occupational health issues, occupational safety and health (OHS) is vital. Indonesia has seen a significant increase in the number of workplace accidents in the last two years. According to data from the National Social Security Agency (BPJS Kesehatan), the number has risen 55.2% from the previous year. Sebagai bukti betapa pentingnya manajemen OHS, industri manufaktur dan pembangunan bertanggung jawab atas 63.6% dari semua workplace accidents. As a manufacturing company that plays a major role in the Indonesian economy, PT. Pagilaran must establish an effective OHS system to protect its employees and ensure that the production process runs safely. Hazard Identification, Risk Assessment, dan Risk Control (HIRARC) method was used to identify hazards, assess risks, and control risks in the production process. The focus of this study is on the dry sorting section of the Black Tea processing process at PT. Pagilaran, where there are several inadequate factors that increase the risk of workplace accidents. The production process that involves a lot of labor, tools, and materials has the potential to cause significant hazards. By conducting an in-depth creating a safer and more productive work environment.